A VLP Library of C-Terminally Truncated Hepatitis B Core Proteins: Correlation of RNA Encapsidation with a Th1/Th2 Switch in the Immune Responses of Mice - Sominskaya, Irina; Skrastina, Dace; Petrovskis, Ivars; Dishlers, Andris; Berza, Ieva; Mihailova, Maria; Jansons, Juris; Akopjana, Inara; Stahovska, Irina; Dreilina, Dzidra; Ose, Velta; Pumpens, Paul (PLOS ONE, 2013)
An efficient pBR327- and Ptrp-based E. coli expression system was used to generate a large-scale library of virus like particles (VLP) formed by recombinant hepatitis B virus (HBV) core (HBc) protein derivatives. To construct the library, the gene of HBc protein of the genotype D/subtype ayw2 virus was gradually truncated from the 3`-end and twenty-two HBc variants (with truncation up to 139 aa) were expressed at high levels. The proteins were purified by salt precipitation and gel filtration. Background RNA binding was observed for VLPs formed by HBc1-149, which lacked all C-terminal Arg blocks, and the addition of three Arg residues (HBc1-152) only slightly increased RNA binding. The presence of two Arg blocks (proteins HBc1-162 and HBc1-163) resulted in approximately half of the typical level of RNA binding, and the presence of three blocks (protein HBc1-171) led to approximately 85% of the typical level of binding. Only a small increase in the level of RNA binding was found for the HBc1-175 VLPs, which contained all four Arg blocks but lacked the last 8 aa of the full-length HBc protein. VLPs containing high levels of RNA had higher antigenicity according to an ELISA with anti-HBc mAbs than the VLPs formed by HBc variants without C-terminal Arg blocks and lacking RNA. The results indicate that the VLPs were stabilised by nucleic acids. The immunogenicity in BALB/c mice was comparable for VLPs formed by different HBc proteins, but a clear switch from a Th1 response to a Th2 response occurred after the loss of encapsidated RNA. We did not observe significant differences in lymphocyte proliferation in vitro for the tested VLP variants; however, the loss of RNA encapsidation correlated with a decreased level of IFN-γ induction, which is a measure of the potential CTL activity of immunogens.